Thrombotic Complications during Interventional Lung Assist: Case Series - Kim, Eun Jung; Cho, Woo Hyun; Ahn, Eun Young; Ryu, Dae Gon; Lee, Seung Eun; Jeon, Doo Soo; Kim, Yun Seong; Son, Bong Soo; Kim, Do Hyung (Tuberculosis and respiratory diseases, 2015)
Interventional lung assist (iLA) effectively reduces CO2 retention and allows protective ventilation in cases of life-threatening hypercapnia. Despite the clinical efficacy of iLA, there are a few major limitations associated with the use of this approach, such as bleeding, thrombosis, and catheter-related limb ischemia. We presented two cases in which thrombotic complications developed during iLA. We demonstrated the two possible causes of thrombotic complications during iLA; stasis due to low blood flow and inadequate anticoagulation.